Maternal attitudes, beliefs and practices related to the feeding and nutritional status of schoolchildren - PEDROSO, Jéssica; TORAL, Natacha; Bauermann GUBERT, Muriel (Revista de Nutrição, 2023)
Objective To analyze the relationship between the maternal attitudes, beliefs and practices and the children’s food consumption and nutritional status. Methods A cross-sectional study of 563 mother-child pairs. Mothers answered an online questionnaire that collected the following information: sociodemographic data, maternal nutritional status, the child’s food consumption (evaluated through the Food Frequency Questionnaire and the School Child Diet Index), and maternal attitudes, beliefs and practices about the schoolchildren’s eating (assessed through the Child Feeding Questionnaire). Children had their anthropometric measurements evaluated for the interpretation of the nutritional status. Results Mothers who considered their children to be bigger (ORaj=6.60) and who worried more about their children’s weight (ORaj=3.47) presented greater chances of having overweight children. Mothers with a greater perception of responsibility (ORaj=0.57) and who put more pressure in their children to eat (ORaj=0.38) presented lower chances of having overweight children. The majority of children consumed high-quality food (77.4%). Mothers who more closely monitored their children’s food consumption were 2.79 times more likely to have their children eating high-quality food. Conclusion Nutritional interventions should focus on stimulating the parents’ sense of responsibility for the child’s nutrition, as well as on promoting the frequent monitoring of the child’s food intake.